Hubungan pengetahuan ibu tentang diare dan perilaku memasak air minum dengan kejadian diare balita di Puskesmas Baringin Kabupaten Tapin tahun 2014 - Budi Hairani; Suriani Suriani; Dicky Andiarsa; Juhairiyah Juhairiyah (Balai Litbangkes Tanah Bumbu, 2017)
Diarrhea is still a health problem in Indonesia especially those that occur at the age of toddler or children because it can cause mortality. The objective of this study was to find out the relationship among mother knowledge with occurrence diarhea and relationship habit of mother toddler in cook household drinking water with occurrence diarhea of toddler were get medical treatment in Baringin public health center. This study was analytic method with cross sectional approach and data collected by questionnaire. This study were get 80 respondent mother who had brought their toddlers at Baringin public health centers in the period January-July 2014 and domiciled in the Baringin public health center work area .The result of statistic used chi square of obtain that was a relationship between knowledge with occurrence diarhea (P = 0,000 < α = 0,05) and relationship between habit of mother toddler in cook household drinking water with occurrence diarhea of toddler were get medical treatment in Baringin public health center (P = 0,000 < α = 0,05). Based on the results of this study suggested an increased implementation of health information by health centers mainly around diarrheal disease and the importance of good hygiene practices, as well as boiling drinking water properly as the prevention of diarrhea.